Employing the Stabbing Word Game to Mastery of Arabic Vocabulary for Seventh Grade Students at Islamic Middle School Gresik - Muh Sabilar Rosyad; Robi'atul Adawiyah; Muhammad Hafidz (Universitas Islam Tribakti Lirboyo, Kediri, 2024)
This modest research seeks to highlight the excitement of the